A halogen-free flame-retardant TPU composite material and preparation method thereof

By using modified flame retardant and ultraviolet absorber in TPU materials, the insulating foam layer and high-quality carbon layer are formed, which solves the problems of flammability and aging of TPU materials, and achieves good flame retardant, heat resistance and UV resistance of halogen-free flame retardant TPU composite materials.

CN119220087BActive Publication Date: 2025-02-28JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411720386.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

TPU materials are flammable, have poor flame retardancy, and are prone to aging, which limits their application in areas with clear requirements for flame retardancy.

Method used

Using modified flame retardant and ultraviolet absorber, the heat-insulating foam layer is formed by dehydrating the ammonium polyphosphate in the modified flame retardant. Intermediate 2 promotes the early degradation and carbonization of the TPU composite material, forming a high-quality carbon layer. Combined with the role of the ultraviolet absorber, the flame retardant, heat resistance and ultraviolet resistance of the composite material are enhanced.

Benefits of technology

It achieves good flame retardant and heat resistance of halogen-free flame retardant TPU composite materials, and has excellent UV resistance, which extends the service life of the material and reduces the possibility of fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a halogen-free flame-retardant TPU composite material and a preparation method thereof, and belongs to the technical field of polymer materials. The halogen-free flame-retardant TPU composite material comprises, by weight, 3-10 parts of a modified flame retardant, 2-10 parts of phenoxy cyclophosphazene, 80-100 parts of TPU particles, 90 parts of N,N-dimethylformamide, 0.8-1.2 parts of an ultraviolet absorber, and 2.5-3.5 parts of a lubricant; in the modified flame retardant, ammonium polyphosphate is heated to polyphosphoric acid, which is heat-insulating and flame-retardant, improves the comprehensive performance of the material, and the quaternary ammonium salt structure and the carbamate bond synergistically enhance the flame retardant and heat-resistant performance of the material; in the ultraviolet absorber, cyanuric chloride and benzotriazole intermediates absorb ultraviolet rays, reduce the damage of ultraviolet rays to the material, and enhance aging resistance and toughness; the halogen-free flame-retardant TPU composite material prepared by the present invention not only has good flame retardant and heat-resistant effects, but also has excellent anti-ultraviolet performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a halogen-free flame-retardant TPU composite material and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane elastomer (TPU) is a new type of organic polymer synthetic material. Due to its excellent mechanical properties, tear strength, wear resistance and elongation recovery, it has shown broad application prospects in many fields such as injection molding products, wires and cables, medicine, and footwear.

[0003] However, TPU is very easy to burn, with intense flames and thick black smoke, large heat release, and severe melting droplets, which limits its application in some fields with clear requirements for flame retardancy. In the prior art, in order to improve the flame retardancy of TPU in an environmentally friendly way, halogen-free flame retardants are usually added to TPU, but for halogen-free flame retardants, a high content is usually required. This high addition content weakens the tensile strength, elongation at break, etc. of thermoplastic polyurethane elastomers, resulting in poor overall performance; in addition, TPU materials are easily affected by ultraviolet rays and are prone to aging. They will gradually become hard, brittle, and lose elasticity when exposed to air for a long time, and they are prone to softening and deformation at high temperatures. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a halogen-free flame-retardant TPU composite material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A halogen-free flame-retardant TPU composite material, comprising the following raw materials in parts by weight: 3-10 parts of a modified flame retardant, 2-10 parts of phenoxy cyclophosphazene, 80-100 parts of TPU particles, 90 parts of N,N-dimethylformamide, 0.8-1.2 parts of an ultraviolet absorber, and 2.5-3.5 parts of a lubricant;

[0007] The lubricant is pentaerythritol ester.

[0008] The modified flame retardant is prepared by the following method:

[0009] Step A1: 4-(dimethylaminomethyl)phenol and toluene diisocyanate were mixed evenly, and dibutyltin dilaurate was added under nitrogen environment, and the mixture was reacted at 150° C. for 1 h, and then placed in a torque rheometer to continue the reaction for 3 h to obtain intermediate 1;

[0010] Further, the mass ratio of 4-(dimethylaminomethyl)phenol, toluene diisocyanate, and dibutyltin dilaurate is 12.29-14.01:15.36-19.65:0.08-0.12;

[0011] Step A2: Intermediate 1, 6-chloro-1-hexene and methanol were mixed, refluxed for 24 hours, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and N,N-dimethylformamide were added, stirred at 150° C. for 9 hours, filtered at room temperature, washed, and vacuum dried at 60° C. for 24 hours to obtain intermediate 2;

[0012] Further, the usage ratio of intermediate 1, 6-chloro-1-hexene, methanol, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and N,N-dimethylformamide is 1-2 mol: 2-4 mol: 2 mL: 2-4 mol: 200-220 mL;

[0013] Step A3: evenly disperse ammonium polyphosphate in deionized water, add intermediate 2 and mix, stir at 40° C. for 1-2 hours, centrifuge, wash, and dry in a vacuum oven at 80° C. for 12 hours to obtain a modified flame retardant;

[0014] Furthermore, the usage ratio of ammonium polyphosphate, deionized water and intermediate 2 is 18-22 g: 180-210 mL: 10.4-12.3 g.

[0015] The ultraviolet absorber is prepared by the following method:

[0016] Step B1: Mix 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, dichloromethane, NaOH solution and tetrabutylammonium bromide, and stir at room temperature for 30 minutes to obtain a mixed solution;

[0017] Further, the dosage ratio of 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, dichloromethane, NaOH solution, and tetrabutylammonium bromide is 2.6-3 g: 20-25 mL: 2.5-3 mL: 0.02 g, and the mass fraction of NaOH solution is 50%;

[0018] Step B2: Mix cyanuric chloride and dichloromethane evenly, divide into three equal parts, and pour into the mixed solution in turn, wherein the first part is added dropwise in a brine ice bath, and then the second part is added dropwise after the temperature is raised to 10°C, and the third part is added dropwise after the temperature is raised to 25°C. After the addition is completed, continue to react for 2 hours, wash, and dry to obtain a compound;

[0019] Further, the dosage ratio of cyanuric chloride, dichloromethane and mixed solution is 1.0 g: 20 mL: 25-30 mL;

[0020] Step B3: The compound and chlorobenzene were mixed, stirred for 1 hour, anhydrous aluminum chloride was added in an ice water bath, stirred for 30 minutes, and then m-xylene was slowly added dropwise, and reacted at 80°C for 2 hours to obtain a UV absorber;

[0021] Furthermore, the usage ratio of the compound, chlorobenzene, anhydrous aluminum chloride and m-xylene is 0.1-0.12 mol: 250 mL: 40.00 g: 21.20-24.1 g.

[0022] A method for preparing a halogen-free flame-retardant TPU composite material comprises the following steps:

[0023] S1: The modified flame retardant, phenoxy cyclophosphazene and N,N-dimethylformamide are mixed, ultrasonicated for 30 minutes, heated to 85°C, TPU particles, ultraviolet absorber and lubricant are slowly added, mixed evenly, and rotary evaporated to obtain a mixture;

[0024] S2: The mixture is extruded and granulated through a twin-screw extruder, the screw temperature of the extruder is set to 160-190° C., and the rotation speed is 400 r / min, to obtain a halogen-free flame-retardant TPU composite material.

[0025] Beneficial effects of the present invention:

[0026] The modified flame retardant prepared by the invention comprises the following steps: firstly, the isocyanate bond of toluene diisocyanate and the hydroxyl group of 4-(dimethylaminomethyl)phenol are reacted to form a carbamate bond to generate an intermediate 1; secondly, under the action of a catalyst methanol, the chlorine atom of 6-chloro-1-hexene is used to cause the intermediate 1 to undergo a quaternary ammonium salt reaction; then, the carbon-carbon double bond of 6-chloro-1-hexene is reacted with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to form an intermediate 2 with a positive charge; and finally, the electrostatic action between the positive charge of the intermediate 2 and the negative charge of ammonium polyphosphate is used to prepare the modified flame retardant. In the modified flame retardant, ammonium polyphosphate is dehydrated into polyphosphoric acid by heat, which promotes carbonization of the surface of organic matter to form a heat-insulating foam layer, effectively isolates air and heat, and achieves a flame retardant effect; intermediate 2 promotes the early degradation and carbonization of TPU composite materials to form a high-quality carbon layer, prevents the transfer of oxygen, heat and combustibles, and the phosphorus-containing free radicals and non-flammable gases generated by its decomposition inhibit combustion in the gas phase; the quaternary ammonium salt structure and the carbamate bond of intermediate 2 synergistically enhance the flame retardant and heat-resistant properties of the composite material; among them, the phosphorus-nitrogen flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, as a phosphaphenanthrene compound with high thermal stability, promotes the formation of a dense and continuous carbon layer during combustion, effectively isolates oxygen, blocks heat and combustible gas exchange, inhibits combustion, and also synergistically flame retards with the phosphorus-oxygen double bond to extend its service life; in addition, the modified flame retardant prepared by the present invention is halogen-free, helps to reduce environmental pollution and damage to the ecosystem, is harmless to human health, and achieves sustainable development.

[0027] The ultraviolet absorber prepared by the present invention firstly reacts the chlorine atom of cyanuric chloride with the hydroxyl group of 2-[2-hydroxy-5-tert-octylphenyl)benzotriazole under the action of dichloromethane to generate a benzotriazole compound; and then the chlorine atom of the benzotriazole compound reacts with meta-xylene to synthesize the ultraviolet absorber. In the ultraviolet absorber, the isotriazine cyanuric chloride contains a conjugated π electron system and an ortho-substituent, which can effectively absorb ultraviolet rays and convert them into heat energy through intramolecular reaction, thereby preventing oxidation and chain breaking caused by ultraviolet rays, protecting the material from ultraviolet damage, extending its service life and enhancing stability; in addition, cyanuric chloride can maintain high efficiency in a wide temperature range, absorb ultraviolet rays in sunlight and fluorescent light sources, release energy in the form of heat energy or harmless low-energy radiation, and avoid photophysical and photochemical decomposition due to ultraviolet excitation. At the same time, the conjugated double bonds and aromatic rings of the benzotriazole intermediate can efficiently absorb ultraviolet rays in different wavelength ranges, and convert ultraviolet energy into heat energy or light energy, significantly reducing the damage of ultraviolet rays to the TPU composite material, enhancing aging resistance, and thus improving toughness. ‌‌

[0028] The invented halogen-free flame-retardant TPU composite material not only has good flame retardant and heat-resistant effects, but also has excellent UV resistance. It can effectively inhibit the combustion process, extend the service life of the material, reduce the possibility of fire, and effectively protect human health. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1: A method for preparing a halogen-free flame-retardant TPU composite material, specifically comprising the following steps:

[0031] S1: Weigh the raw materials by weight, including 3 parts of modified flame retardant (prepared in this example), 2 parts of phenoxy cyclophosphazene, 80 parts of TPU particles, 90 parts of N,N-dimethylformamide, 0.8 parts of ultraviolet absorber (prepared in this example), and 2.5 parts of lubricant; mix the modified flame retardant, phenoxy cyclophosphazene and N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, heat to 85°C, slowly add TPU particles, ultraviolet absorber and lubricant, mix well, and perform rotary evaporation to obtain a mixture;

[0032] S2: Extruding the mixture into granules through a twin-screw extruder, the screw temperature of the extruder is set to 160° C., and the rotation speed is 400 r / min, to obtain a halogen-free flame-retardant TPU composite material;

[0033] The modified flame retardant is prepared by the following method:

[0034] Step A1: 12.29 g of 4-(dimethylaminomethyl)phenol and 15.36 g of toluene diisocyanate were mixed evenly, and 0.08 g of dibutyltin dilaurate was added under a nitrogen environment. The mixture was reacted at 150° C. for 1 h, and then placed in a torque rheometer to continue the reaction for 3 h to obtain an intermediate 1;

[0035] Step A2: 1 mol of intermediate 1, 2 mol of 6-chloro-1-hexene and 2 mL of methanol were mixed, refluxed for 24 h, and then 2 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 200 mL of N,N-dimethylformamide were added and mixed, stirred at 150° C. for 9 h, filtered at room temperature, washed, and vacuum dried at 60° C. for 24 h to obtain intermediate 2;

[0036] Step A3: 18 g of ammonium polyphosphate was evenly dispersed in 180 mL of deionized water, and 10.4 g of intermediate 2 was added and mixed, stirred at 40° C. for 1 h, centrifuged, washed, and dried in a vacuum oven at 80° C. for 12 h to obtain a modified flame retardant;

[0037] The ultraviolet absorber is prepared by the following method:

[0038] Step B1: 2.6 g of 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 20 mL of dichloromethane, 2.5 mL of NaOH solution and 0.02 g of tetrabutylammonium bromide were mixed, and stirred at room temperature for 30 min to obtain a mixed solution, wherein the mass fraction of the NaOH solution was 50%;

[0039] Step B2: 1.0 g of cyanuric chloride and 20 mL of dichloromethane were mixed evenly, divided into three equal parts, and poured into 25 mL of the mixed solution in sequence, wherein the first part was added dropwise in a brine ice bath, and then the second part was added dropwise after the temperature was raised to 10° C., and the third part was added dropwise after the temperature was raised to 25° C. After the addition was completed, the reaction was continued for 2 h, washed, and dried to obtain a compound;

[0040] Step B3: Mix 0.1 mol of the compound and 250 mL of chlorobenzene, stir for 1 hour, add 40.00 g of anhydrous aluminum chloride in an ice-water bath, stir for 30 minutes, then slowly add 21.20 g of m-xylene dropwise, react at 80°C for 2 hours to obtain a UV absorber.

[0041] Embodiment 2: A method for preparing a halogen-free flame-retardant TPU composite material, comprising the following steps:

[0042] S1: Weigh the raw materials by weight, including 7 parts of modified flame retardant (prepared in this example), 6 parts of phenoxy cyclophosphazene, 90 parts of TPU particles, 90 parts of N,N-dimethylformamide, 1 part of ultraviolet absorber (prepared in this example), and 3 parts of lubricant; mix the modified flame retardant, phenoxy cyclophosphazene and N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, heat to 85°C, slowly add TPU particles, ultraviolet absorber and lubricant, mix well, and perform rotary evaporation to obtain a mixture;

[0043] S2: Extruding the mixture into granules through a twin-screw extruder, the screw temperature of the extruder is set to 175° C., and the rotation speed is 400 r / min, to obtain a halogen-free flame-retardant TPU composite material;

[0044] Step A1: 13.6 g of 4-(dimethylaminomethyl)phenol and 17.65 g of toluene diisocyanate were mixed evenly, and 0.1 g of dibutyltin dilaurate was added under nitrogen environment, and the mixture was reacted at 150° C. for 1 h, and then placed in a torque rheometer to continue the reaction for 3 h to obtain intermediate 1;

[0045] Step A2: 1.5 mol of intermediate 1, 3 mol of 6-chloro-1-hexene and 2 mL of methanol were mixed, refluxed for 24 h, then 3 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 210 mL of N,N-dimethylformamide were added, stirred at 150° C. for 9 h, filtered at room temperature, washed, and vacuum dried at 60° C. for 24 h to obtain intermediate 2;

[0046] Step A3: 20 g of ammonium polyphosphate was uniformly dispersed in 195 mL of deionized water, and 11.2 g of intermediate 2 was added and mixed, stirred at 40° C. for 1.5 h, centrifuged, washed, and dried in a vacuum oven at 80° C. for 12 h to obtain a modified flame retardant;

[0047] The ultraviolet absorber is prepared by the following method:

[0048] Step B1: 2.8 g of 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 22.5 mL of dichloromethane, 2.7 mL of NaOH solution and 0.02 g of tetrabutylammonium bromide were mixed, and stirred at room temperature for 30 min to obtain a mixed solution, wherein the mass fraction of the NaOH solution was 50%;

[0049] Step B2: 1.0 g of cyanuric chloride and 20 mL of dichloromethane were mixed evenly, divided into three equal parts, and poured into 27 mL of the mixed solution in sequence, wherein the first part was added dropwise in a brine ice bath, and then the temperature was raised to 10° C. and the second part was added dropwise, and the temperature was raised to 25° C. and the third part was added dropwise. After the addition was completed, the reaction was continued for 2 h, washed, and dried to obtain a compound;

[0050] Step B3: 0.11 mol of the compound was mixed with 250 mL of chlorobenzene, and stirred for 1 h. Then, 40.00 g of anhydrous aluminum chloride was added in an ice-water bath, and stirred for 30 min. Then, 22.6 g of m-xylene was slowly added dropwise, and reacted at 80° C. for 2 h to obtain a UV absorber.

[0051] Embodiment 3: A method for preparing a halogen-free flame-retardant TPU composite material, specifically comprising the following steps:

[0052] S1: Weigh the raw materials by weight, including 10 parts of modified flame retardant (prepared in this example), 10 parts of phenoxy cyclophosphazene, 100 parts of TPU particles, 90 parts of N,N-dimethylformamide, 1.2 parts of ultraviolet absorber (prepared in this example), and 3.5 parts of lubricant; mix the modified flame retardant, phenoxy cyclophosphazene and N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, heat to 85° C., slowly add TPU particles, ultraviolet absorber and lubricant, mix well, and perform rotary evaporation to obtain a mixture;

[0053] S2: Extruding the mixture into granules through a twin-screw extruder, the screw temperature of the extruder is set to 190° C., and the rotation speed is 400 r / min, to obtain a halogen-free flame-retardant TPU composite material;

[0054] Step A1: 14.01 g of 4-(dimethylaminomethyl)phenol and 19.65 g of toluene diisocyanate were mixed evenly, and 0.12 g of dibutyltin dilaurate was added under a nitrogen environment. The mixture was reacted at 150° C. for 1 h, and then placed in a torque rheometer to continue the reaction for 3 h to obtain an intermediate 1;

[0055] Step A2: 2 mol of intermediate 1, 4 mol of 6-chloro-1-hexene and 2 mL of methanol were mixed, refluxed for 24 h, then 4 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 220 mL of N,N-dimethylformamide were added, stirred at 150° C. for 9 h, filtered at room temperature, washed, and vacuum dried at 60° C. for 24 h to obtain intermediate 2;

[0056] Step A3: 22 g of ammonium polyphosphate was evenly dispersed in 210 mL of deionized water, and 12.3 g of intermediate 2 was added and mixed, stirred at 40° C. for 2 h, centrifuged, washed, and dried in a vacuum oven at 80° C. for 12 h to obtain a modified flame retardant;

[0057] The ultraviolet absorber is prepared by the following method:

[0058] Step B1: 3 g of 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 25 mL of dichloromethane, 3 mL of NaOH solution and 0.02 g of tetrabutylammonium bromide were mixed, and stirred at room temperature for 30 min to obtain a mixed solution, wherein the mass fraction of the NaOH solution was 50%;

[0059] Step B2: 1.0 g of cyanuric chloride and 20 mL of dichloromethane were mixed evenly, divided into three equal parts, and poured into 30 mL of the mixed solution in sequence, wherein the first part was added dropwise in a brine ice bath, and then the temperature was raised to 10° C. and the second part was added dropwise, and the temperature was raised to 25° C. and the third part was added dropwise. After the addition was completed, the reaction was continued for 2 h, washed, and dried to obtain a compound;

[0060] Step B3: Mix 0.12 mol of the compound and 250 mL of chlorobenzene, stir for 1 hour, add 40.00 g of anhydrous aluminum chloride in an ice-water bath, stir for 30 minutes, then slowly dropwise add 24.1 g of m-xylene, react at 80°C for 2 hours to obtain a UV absorber.

[0061] Comparative Example 1: This comparative example is a halogen-free flame-retardant TPU composite material. The difference from Example 3 is that an equal amount of magnesium hydroxide is used to replace the modified flame retardant prepared in Example 3, and the rest are the same.

[0062] Comparative Example 2: This comparative example is a halogen-free flame-retardant TPU composite material. The difference from Example 3 is that an equal amount of ultraviolet blocker nano barium sulfate is used to replace the ultraviolet absorber prepared in Example 3, and the rest is the same.

[0063] Performance test: The halogen-free flame-retardant TPU composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were cut into standard test sizes, and irradiated for 40 hours at a vertical distance of 10 cm using a UVC-LED disinfection lamp (30 W, 254 nm wavelength), and the color difference before and after UVC-LED irradiation was detected according to the CIE1976L*a*b* standard; the flame retardant properties were tested according to GB / T2408-2008; after using an aging box at 136°C for 168 hours, the retention rate of tensile strength and elongation at break was tested after being placed in a standard laboratory (23°C, 50% humidity) for 24 hours; the test results are shown in the following table:

[0064] From the test data in the table, it can be seen that the halogen-free flame retardant TPU composite material prepared in Example 1 not only has good heat resistance, effectively guarantees the safety of the material, but also has excellent UV resistance. It can also be seen from the above table that the halogen-free flame retardant TPU composite material prepared in the present invention has excellent flame retardant effect, effectively inhibits the combustion process, reduces the possibility of fire, and prolongs the service life of the material.

[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a halogen-free flame-retardant TPU composite material, characterized in that: The following steps are involved: S1: weigh the raw materials by weight, including 3-10 parts of modified flame retardant, 2-10 parts of phenoxy cyclophosphazene, 80-100 parts of TPU particles, 90 parts of N,N-dimethylformamide, 0.8-1.2 parts of ultraviolet absorber, and 2.5-3.5 parts of lubricant; mix the modified flame retardant, phenoxy cyclophosphazene and N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, heat to 85°C, slowly add TPU particles, ultraviolet absorber and lubricant, mix well, and perform rotary evaporation to obtain a mixture; S2: Extruding the mixture into granules through a twin-screw extruder, the screw temperature of the extruder is set to 160-190° C., and the rotation speed is 400 r / min, to obtain a halogen-free flame-retardant TPU composite material; The modified flame retardant is prepared by the following method: Step A1: 4-(dimethylaminomethyl)phenol and toluene diisocyanate were mixed evenly, dibutyltin dilaurate was added under nitrogen environment, reacted at 150°C for 1 hour, and then placed in a torque rheometer to continue the reaction for 3 hours to obtain an intermediate 1,4-(dimethylaminomethyl)phenol, toluene diisocyanate, and dibutyltin dilaurate in a mass ratio of 12.29-14.01:15.36-19.65:0.08-0.12; Step A2: Intermediate 1, 6-chloro-1-hexene and methanol are mixed, refluxed for 24 hours, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and N,N-dimethylformamide are added and mixed, stirred at 150°C for 9 hours, filtered and washed at room temperature, and vacuum dried at 60°C for 24 hours to obtain intermediate 2. The amount ratio of intermediate 1, 6-chloro-1-hexene, methanol, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and N,N-dimethylformamide is 1-2 mol: 2-4 mol: 2 mL: 2-4 mol: 200-220 mL; Step A3: Disperse ammonium polyphosphate evenly in deionized water, add intermediate 2 and mix, stir at 40°C for 1-2h, centrifuge, wash, and dry in a vacuum oven at 80°C for 12h to obtain a modified flame retardant. The dosage ratio of ammonium polyphosphate, deionized water, and intermediate 2 is 18-22g:180-210mL:10.4-12.3g.

2. The method for preparing a halogen-free flame-retardant TPU composite material according to claim 1, characterized in that: The ultraviolet absorber is prepared by the following method: Step B1: Mix 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, dichloromethane, NaOH solution and tetrabutylammonium bromide, and stir at room temperature for 30 minutes to obtain a mixed solution; Step B2: Mix cyanuric chloride and dichloromethane evenly, divide into three equal parts, and pour into the mixed solution in turn, wherein the first part is added dropwise in a brine ice bath, and then the second part is added dropwise after the temperature is raised to 10°C, and the third part is added dropwise after the temperature is raised to 25°C. After the addition is completed, continue to react for 2 hours, wash, and dry to obtain a compound; Step B3: Mix the compound and chlorobenzene, stir for 1 hour, add anhydrous aluminum chloride in an ice-water bath, stir for 30 minutes, then slowly drop m-xylene, react at 80°C for 2 hours to obtain a UV absorber.

3. The method for preparing a halogen-free flame-retardant TPU composite material according to claim 2, characterized in that: In step B1, the usage ratio of 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, dichloromethane, NaOH solution and tetrabutylammonium bromide is 2.6-3 g: 20-25 mL: 2.5-3 mL: 0.02 g, and the mass fraction of NaOH solution is 50%.

4. The method for preparing a halogen-free flame-retardant TPU composite material according to claim 2, characterized in that: In step B2, the usage ratio of cyanuric chloride, dichloromethane and mixed solution is 1.0g:20mL:25-30mL.

5. The method for preparing a halogen-free flame-retardant TPU composite material according to claim 2, characterized in that: In step B3, the usage ratio of the compound, chlorobenzene, anhydrous aluminum chloride and m-xylene is 0.1-0.12 mol: 250 mL: 40.00 g: 21.20-24.1 g.

6. A halogen-free flame-retardant TPU composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Benzotriazole compound ultraviolet light absorber as well as preparation method and application thereof

    CN107089973A

  • Preparation method of ultraviolet light absorber UV-1600 intermediate

    CN110372620A

  • Halogen-free flame-retardant TPU composite material and preparation method thereof

    CN115093694A